Midkine promotes renal fibrosis by stabilizing C/EBPβ to facilitate endothelial-mesenchymal transition - Cuidi Xu; Juntao Chen; Lifei Liang; Siyue Chen; Xinhao Niu; Ruirui Sang; Cheng Yang; Ruiming Rong (Communications Biology, 2024)
Abstract Numerous myofibroblasts are arisen from endothelial cells (ECs) through endothelial to mesenchymal transition (EndMT) triggered by TGF-β. However, the mechanism of ECs transforms to a different subtype, or whether there exists an intermediate state of ECs remains unclear. In present study, we demonstrate Midkine (MDK) mainly expressed by CD31 + ACTA2+ECs going through partial EndMT contribute greatly to myofibroblasts by spatial and single-cell transcriptomics. MDK is induced in TGF-β treated ECs, which upregulates C/EBPβ and increases EndMT genes, and these effects could be reversed by siMDK. Mechanistically, MDK promotes the binding ability of C/EBPβ with ACTA2 promoter by stabilizing the C/EBPβ protein. In vivo, knockout of Mdk or conditional knockout of Mdk in ECs reduces EndMT markers and significantly reverses fibrogenesis. In conclusion, our study provides a mechanistic link between the induction of EndMT by TGF-β and MDK, which suggests that blocking MDK provides potential therapeutic strategies for renal fibrosis.